SLAP Is a Negative Regulator of FcεRI Receptor-Mediated Signaling and Allergic Response - Sharma, Namit; Ponce, Marta; Kaul, Savar; Pan, Zhongda; Berry, Donna M.; Eiwegger, Thomas; McGlade, Catherine J. (Frontiers in Immunology, 2019)
Binding of antigen to IgE-high affinity FcεRI complexes on mast cells and basophils results in release of preformed mediators such as histamine and de novo synthesis of cytokines causing allergic reactions. Src-like adapter protein (SLAP) functions co-operatively with c-Cbl to negatively regulate signaling downstream of T cell receptor, B cell receptor, and receptor tyrosine kinases (RTK). Here, we investigated the role of SLAP in FcεRI-mediated mast cell signaling using bone marrow derived mast cells (BMMCs) from SLAP knock out (SLAP KO) mice. Mature SLAP-KO BMMCs displayed significantly enhanced antigen induced degranulation and synthesis of IL-6, TNFα and MCP-1 compared to wild type (WT) BMMCs. In addition, SLAP KO mice displayed an enhanced passive cutaneous anaphylaxis response. In agreement with a negative regulatory role, SLAP KO BMMCs showed enhanced FcɛRI-mediated signaling to downstream effector kinases, Syk, Erk and Akt. Recombinant GST-SLAP protein binds to FcɛRIβ chain and to Cbl-b in mast cell lysates suggesting a role in FcɛRI down regulation. In addition, the ubiquitination of FcɛRIγ chain and antigen mediated down regulation of FcεRI is impaired in SLAP KO BMMCs compared to wild type. In line with these findings, stimulation of peripheral blood human basophils with FcɛRIα antibody or a clinically relevant allergen resulted in increased SLAP expression. Together these results indicate that SLAP is a dynamic regulator of IgE-FcɛRI signaling that limits allergic responses.